Cambridge handbook of research approaches to business ethics and corporate responsibility - Werhane, Patricia Hogue 1935-; Freeman, R. Edward 1951-; Dmytriyev, Sergiy (Cambridge University Press, 2017)
Machine generated contents note: Introduction; Part I: Philosophical Approaches; Historical Approaches: 1. The use of historical figures as a research approach Patricia H. Werhane, R. Edward Freeman and Sergiy Dmytriyev; 2. History as methodology in business ethics: lessons from Aristotle Edwin M. Hartman; 3. The role of continental philosophy in business ethics research Mollie Painter Morland; Normative Approaches; 4. Research in normative business ethics: a coherence approach Richard T. De George; 5. The universalist approach and Kant in business ethics Norman E. Bowie; Part II. Empirical Approaches; Qualitative Approaches: 6. Normative assessments in empirical business ethics research: toward a methodological bridge across the ontological gap Sarah Margaretha Jastram and Damian Baumlisberger; 7. Descriptive ethics: a neglected methodological domain in business and applied ethics Wesley Cragg; 8. Grounded theory in business ethics David Bevan and Angelo Carlo S. Carrascoso; 9. Discourse analysis as a method for business ethics and corporate responsibility research Anna Heikkinen, Johanna Kujala, Matias Laine and Hannele Makela; Quantitative and Experimental Approaches; 10. Quantitative content analysis as a method for business ethics research Irina Lock and Peter Seele; 11. Experiments in business ethics Helet Botha; Contemporary Approaches; 12. Mixed methodologies, full-cycle research and the shortcomings of behavioral ethics Scott Sonenshein and Katherine DeCelles; 13. Applying neuroscience to business ethics Filomena Sabatella, Nicola Pless and Thomas Maak; 14. Wide reflective equilibrium as a case-based research approach to business ethics Patricia H. Werhane; Case Study Approaches; 15. Casuistry as a case-based research approach to business ethics Martin Calkins; 16. Building on actor-network analysis to study corporate social responsibility: conceptual and ++